2021
DOI: 10.1089/apb.21.921099
|View full text |Cite
|
Sign up to set email alerts
|

The Hitchhiker's Guide to Hydrogen Peroxide Fumigation, Part 2: Verifying and Validating Hydrogen Peroxide Fumigation Cycles

Abstract: Introduction: Part 1 of this two-part series describes the use of hydrogen peroxide as a fumigant and compares it with other fumigants on the market. Technical requirements are outlined while considering physical and biological limitations of the system. This second part focuses primarily on the use of process controls to verify and validate hydrogen peroxide fumigations. Finally, a model encompassing the entire fumigation process is presented. Methods: Part 2 of the series focuses on the authors' long-time pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The finding that G. stearothermophilus is the most resistant microorganism to H 2 O 2 is supported by research [74]. Several studies have suggested using G. stearothermophilus spores to validate the aHP process [75], [76]. We used 2.30 × 10 6 G. stearothermophilus ATCC 7953 to represent the most resistant strain to the aHP decontamination process and placed BIs in nine locations for each bus in accordance with the room sterilization protocol by the US Environmental Protection Agency (US EPA) that recommends for testing BI must contain ≥10 6 G. stearothermophilus (ATCC 7953) spores, and test location of BIs must include all corners of the rooms, wall faces, center location, and underneath horizontal surfaces [77].…”
Section: Discussionmentioning
confidence: 81%
“…The finding that G. stearothermophilus is the most resistant microorganism to H 2 O 2 is supported by research [74]. Several studies have suggested using G. stearothermophilus spores to validate the aHP process [75], [76]. We used 2.30 × 10 6 G. stearothermophilus ATCC 7953 to represent the most resistant strain to the aHP decontamination process and placed BIs in nine locations for each bus in accordance with the room sterilization protocol by the US Environmental Protection Agency (US EPA) that recommends for testing BI must contain ≥10 6 G. stearothermophilus (ATCC 7953) spores, and test location of BIs must include all corners of the rooms, wall faces, center location, and underneath horizontal surfaces [77].…”
Section: Discussionmentioning
confidence: 81%
“…H 2 O 2 fumigation offers a highly practical and potentially effective means of decontaminating complex rooms, such as hospital wards or laboratories, as well as items of equipment [3,4], so long as these areas can be safely and effectively sealed off from their surroundings. Consequently, it is a viable option to decontaminate the multiple internal surfaces of EpiShuttle units after they have been used to transfer patients who are potentially suffering from HCID and, therefore, potentially shedding pathogens into their surroundings.…”
Section: Discussionmentioning
confidence: 99%
“…This paper describes a study that aims to validate the decontamination procedure that is applied to the EpiShuttle after each use. While EpiGuard have a manual decontamination procedure for the EpiShuttle that involves wiping with liquid disinfectant, a less 'hands-on' method would involve using a hydrogen peroxide (H 2 O 2 ) vapour fumigation system [3,4], which may also ensure enhanced penetration to all of the parts of the equipment. HCID Units routinely use H 2 O 2 vapour fumigation for other decontamination requirements [5], but they require validation for its use with the EpiShuttle.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the comparable properties of the carrier material should allow easy transferability to HEPA filters. However, there are reasons that speak against such a choice [ 15 ], [ 16 ]. Filter paper is not ideal because it is very likely to absorb the disinfectant, concentrate it and release it over time, leading to false negatives, i.e., spurious inhibition of microbial growth.…”
Section: Discussionmentioning
confidence: 99%